2005
DOI: 10.1080/13651500510028977
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and psychiatric disorders in Hungary

Abstract: Data from the United States and from several European countries show that patients with major mood disorders, schizophrenia and social phobia smoke at significantly higher rates than the general population. However, there are no published results on this field from Central Europe, including Hungary. In the present study, the rate of current and lifetime smoking of the consecutively screened outpatients with DSM-IV unipolar major depression (n=92), bipolar disorder (n=60), schizophrenia (n=80), schizoaffective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…These results were found for a range of timeframes for depression diagnoses and symptoms (e.g., lifetime, past-year, past-month). The results also showed that both men (28,30,38) and women (31,32,35,36,38) with MDD, dysthymia, or depressive symptoms reported significantly higher rates of current/past-year and lifetime smoking when compared with their counterparts without MDD, dysthymia, or depressive symptoms, with the exception of current light smoking which was only significantly higher among females with MDD and not among males with MDD (38). When race/ethnicity was included as a moderator, data from the Health Information National Trends Survey (HINTS) (33) suggested a significant interaction between past 2-week depressive symptoms and smoking status: depressive symptoms were associated with significantly increased smoking levels among White and Hispanic respondents, but there was no link between depression and smoking among Black respondents.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…These results were found for a range of timeframes for depression diagnoses and symptoms (e.g., lifetime, past-year, past-month). The results also showed that both men (28,30,38) and women (31,32,35,36,38) with MDD, dysthymia, or depressive symptoms reported significantly higher rates of current/past-year and lifetime smoking when compared with their counterparts without MDD, dysthymia, or depressive symptoms, with the exception of current light smoking which was only significantly higher among females with MDD and not among males with MDD (38). When race/ethnicity was included as a moderator, data from the Health Information National Trends Survey (HINTS) (33) suggested a significant interaction between past 2-week depressive symptoms and smoking status: depressive symptoms were associated with significantly increased smoking levels among White and Hispanic respondents, but there was no link between depression and smoking among Black respondents.…”
Section: Resultsmentioning
confidence: 75%
“…Adults with MDD or dysthymia reported higher rates of ever smoking (27), current/past-year smoking or nicotine use (4,5,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), and lifetime smoking (4,5,32,39) compared with adults without MDD, dysthymia, or depressive symptoms. These results were found for a range of timeframes for depression diagnoses and symptoms (e.g., lifetime, past-year, past-month).…”
Section: Resultsmentioning
confidence: 94%
“…A study from Turkey also found higher smoking rates in bipolar patients (55.1%) than in the control population (47.3%) (although the difference was not statistically significant, perhaps because of the relatively small sample size and/or the high smoking rate in the general population). A Hungarian study also reported significantly higher rates of current and ever smoking among bipolar patients compared to the general population (Gonzalez-Pinto et al, 1998;Itkin et al, 2001;Uçok et al, 2004;Dome et al, 2005).…”
Section: Epidemiologymentioning
confidence: 89%
“…schizophrenia or schizoaffective disorder, major depressive disorder, bipolar or panic disorder, alcohol/opiate/cocaine/cannabis dependence, attention deficit hyperactivity disorder, or posttraumatic stress disorder) are significantly higher than the smoking rates of the general population. Only a few psychiatric disorders, such as obsessivecompulsive disorder, catatonic subtype of schizophrenia, and autism spectrum disorders are associated with lower rates of smoking than in the average population (Zvolensky and Bernstein, 2005;Bejerot and Nylander, 2003;de Leon and Diaz, 2005;Vanable et al, 2003;Hughes et al, 1986;Wu et al, 2006;Dome et al, 2005;Hapke et al, 2005;Fu et al, 2007b;Bejerot and Humble, 1999;Beratis et al, 2001;Shoptaw et al, 2002;Patkar et al, 2006;Littleton et al, 2007;Agrawal et al, 2008;Wilens et al, 2008a,b). Astonishingly, the 7% of the overall population who have both a psychiatric disorder and are nicotine dependent consume 34% of all cigarettes smoked in the USA.…”
Section: Epidemiology Of Smoking In Psychiatric Patientsmentioning
confidence: 95%
“…In several studies tobacco dependence has been associated with male gender, tertiary level of education, older age, alcohol use disorders [12], bipolar disorder [12, 13], unipolar depression, personality disorders, schizophrenia and schizoaffective disorder [13, 14]. Although the prevalence of tobacco was studied in different populations in sub-Saharan Africa including Ethiopia, little is known about tobacco dependence and associated factors among mental health service users.…”
Section: Introductionmentioning
confidence: 99%